Oxybuoy: constructing a real-time inexpensive hypoxia monitoring platform - Mohd. Nor, Rizal; Nesterenko, Mikhail; Lavrentyev, Peter (Springer Berlin Heidelberg, 2010)
We present a low-cost sensor buoy designed for unattended dissolved oxygen measurement in aquatic environment. We describe the buoy’s architectural design and three experiments that we carried out to demonstrate its viability: a laboratory test in a water tank with controlled oxygen level, a lake deployment and an extensive electric power consumption test. Our experiments indicate the viability of such an approach to dissolved oxygen monitoring and promise further advances in hypoxia studies.